Geomorphological Characteristics of the Massif Prenj - Lepirica, Alen (Acta Carsologica, 2008)
The researched area of the mountain massif Prenj with surface of 463 km2 is located in the zone of high karst of Outer Dinarides of Bosnia and Herzegovina. It is circular mountain morphostructure with assymetrical transversal profile. Developed in Mesozoic subhorizontal layers of limestone and dolomite over 3500 thick, fissured by numerous reverse and normal faults. Prenj is folded-thrusted mountain massif (2103 m a.s.l.) uplifted during neotectonic phase of Dinarides development, structurally represented by three blocks. A high degree of correlation between lithology, fault structures and relief has been determinated. The main fault structures caused by rotation of Prenj blocks which were reflected on different orientations of stretching of the mountain ridges and composite valleys of Neretva, Konjièka Bijela, Mostarska Bijela, Glogo¹nica and Id-bar. Thrusts express tectonic, lithological, and morphological border of the considered mountain with inter mountain Neogene depressions in the North and South. Netectonic movements and dominanting carbonate composition of the terrain have influenced on reticular relief structure of the massif. Linear landforms of ridges formed in karst are neotectonically, rectilinearly and half-arc elongated up to 12 km. In regards to morphogenesis during the Quaternary, the massif is characterized by development: derasional, glacial, periglacial, karstic, fluviokarstic, fluviodenudational and fluvial erosional and accumulational processes and landforms. Finally, geomorphological regionalization of Prenj was made on the basis of the criteria of similarity of morpho-evolutionary, structural-lithological and orographical characteristics.